Slay ride eaudiobook - Francis, Dick (Recorded Books, Inc., 2022)
Dick Francis takes you into the thrilling world of horse racing with this gripping tale about the illusion of film and the reality of murder. Champion jockey Robert Sherman has disappeared right before his wife was about to give birth. And right before he was sure to win the National. A coincidence? British investigator David Cleveland doesn't think so. He's convinced someone made Sherman disappear, but with every answer David gets, the body count rises. And if he isn't careful, the next body might just be his own ...